Penyelesaian Permasalahan Tenaga Kerja Di Kabupaten Minahasa Utara - Tinangon, Edwin Neil; Lumintang, Djefry Welly; Mangowa, Mario Gerson; Kaligis, Royke Yesdaven Jermia (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2024)
Finding legal solutions for labor disputes in North Minahasa Regency (Minuta), particularly at the Manpower Office, is the goal of the study. The use of normative juridical research involves understanding the law as a set of rules or positive norms, as well as laws in addition to interviews and observations, and then reviewing or analyzing secondary data in the form of legal materials, particularly primary legal materials and secondary legal materials. The findings indicate that fewer labor cases—five—than in 2020 and 2021 were submitted to the Minuta of Manpower Office. Upon submission of the instances, the involved parties voluntarily decided to address the issue after they had instructions from the Manpower Office representatives.